Reactivity of the reward system in artists during acceptance and rejection of monetary rewards - Maldonado, Roberto Goya; Gruber, Oliver (Creativity research journal, 2018)
Humans possess an invaluable ability of self-expression that extends into visual, literary, musical, and many other fields of creation. More than any other profession, artists are in close contact with this subdomain of creativity. Probably one of the most intriguing aspects of creativity is its negative correlation with the availability of monetary reward. The aim of this study was to investigate the reactivity of the dopaminergic reward system in artists and nonartist controls using the desire-reason-dilemma (DRD) paradigm, which allows separate evaluation of reactivity to the acceptance and rejection of rewards. Using fMRI, blood-oxygen-level-dependent (BOLD) responses were measured in key regions of the reward system, namely the ventral striatum (VS), the ventral tegmental area (VTA), and the anterior ventral prefrontal cortex (AVPFC). In contrast to controls, artists presented significantly weaker VS activation in reward acceptance. Additionally, they showed stronger suppression of the VS by the AVPFC in reward rejection. No other differences in demographic or behavioral data were evidenced. These results support the existence of characteristic neural traits in artists, who display reduced reactions to monetary reward acceptance and increased reactions to monetary reward rejection.
Gesehen am 14.05.2019